Estudo térmico e vibracional dos cristais de β-alanina pura e dopada com prata - SOUSA, Johnny Clécio Feitosa (2016)
In this work a study on the influence of silver (Ag+ ) in the crystal structure of the crystal β - alanine. The introduction of doping in a crystal lattice can change its physical properties and its growth habit. These changes in the structure can optimize the technological applications of these crystals. The crystals of β - alanine and pure β - alanine doped with silver ions (Ag +) were grown by the method of slow evaporation of solvent resulting in good quality crystals. Characterization was carried measured by X-ray diffraction, thermogravimetry, differential thermal analysis, differential scanning calorimetry and Raman scattering at room temperature and at high temperatures. After twenty days of rest, we obtained the pure and doped crystal growth in a solution with pH 6.2 and 6.8. With the diffractogram of the pure and doped and analyzes the Rietveld method, it was found that at room temperature the β -pure Alanine and doped with Ag + crystallize in the space group of orthorhombic structure P, b, c, a (61) , α, β, γ = 90 °. The refinement of quality parameters were satisfactory, with RWP = 14.32% and S = 1.23 for the pure sample and RWP = 18.16% and S = 1.38. The thermal analysis DTA and TGA showed that pure sample has thermal stability to 180 ° C and a weight loss of 80% between 180ºC and 332ºC with first endothermic event at 202.16 °C. And for the doped mass loss percentage is maintained, but the sample showed a lower thermal stability to 165 ° C first endothermic event at 193.49 ° C. DSC analysis revealed that pure sample undergoes fusion 206.49 ° C and 196.02 ° C in sample doped and that there is no thermal event that features a phase transition before melting. The Raman scattering study was conducted with temperatures in three spectral regions with gradually increasing temperature (40 ° C to 170 ° C). The first 40 cm -1 to 300 cm -1 , corresponding to modes of external vibration the second at 500 cm-1 and 1500 cm-1 and the third at 2800 cm-1 and 3100 cm -1 que are related to the vibration modes internal. The measurements showed that there was a weakening of the intermolecular bonds in the crystal of β - alanine doped with Ag+ ions, and that all the dynamic study is being described by two bands of lower power modes of the network once. Thus, the crystals have good transparency and optical studies can be applied in non-linear optics.